Love Curriculum: Weaving Harmony in Islamic Education - Reni Susanti; Uki Lestari; Nanda Mesrawita; Mira Shalwati; Eva Nursanti; Demina Demina (Yayasan Zia Salsabila, 2026)
This article examines the Love Curriculum as a paradigm of Islamic education that positions rahmah, empathy, tolerance, and social responsibility as the core of the learning process. This discussion is relevant because contemporary Islamic education frequently encounters tension between cognitive achievement, administrative expectations, and the need to cultivate humane moral character. The study applies a qualitative approach through library research. The data were drawn from scholarly articles, books, and related documents concerning the Love Curriculum, humanistic Islamic education, pedagogical love, hidden curriculum, and two supplementary Google Books sources. The data were examined using thematic content analysis involving data reduction, thematic coding, conceptual synthesis, and the formulation of educational implications. The study highlights three principal findings. First, the Love Curriculum should not be reduced to a romanticized policy phrase, since it represents a theo-humanistic framework that integrates reason, conscience, and spirituality. Second, the value of love can be translated into educational practice through Panca Cinta, empathy, compassion, tolerance, justice, respect, cooperation, responsibility, and creativity. Third, harmony in Islamic education cannot rely solely on formal curriculum documents but must also be supported by the hidden curriculum through teacher exemplarity, a safe school or madrasah culture, dialogical learning, and measurable affective assessment. This article concludes that the Love Curriculum may become a transformative strategy for Islamic education when it is consistently reflected in learning objectives, content, methods, institutional culture, and assessment.